Characteristics of wind flow around a target building with different surrounding building layers predicted by CFD simulation. (15th August 2021) - Zheng, Shu; Wang, Yi; (John) Zhai, Zhiqiang; Xue, Yu; Duanmu, Lin
Abstract: This study explored appropriate surrounding building regions that can ensure an accurate prediction of wind flow characteristics around the target building. A validated computational fluid dynamics (CFD) program solving the Reynolds-Averaged Navier Stokes (RANS) equations with k-ε turbulence model is used to investigate the influences of surrounding buildings with different heights, densities and arrangements on the target building. An empirical formula is developed to determine an appropriate spatial domain in simulation for different combinations of building density and height under varying layout modes. The proposed rules are further demonstrated and verified by simulating the wind flow of a target building in Dalian, China. Simulation results confirm that the surrounding building height, density and layout have a considerable impact on the simulated core region and single influencing factor cannot determine a reasonable flow simulation domain. The developed guide can effectively predict the wind flow conditions around buildings with an acceptable modeling accuracy and effort. Highlight: Empirical formula was developed to determine an appropriate spatial domain in simulation for different combinations of building density and height under varying layout modes The proposed rules were further demonstrated and verified by simulating the wind flow of a target building in Dalian, China The developed guide can effectively predict the wind flow conditions around buildings with an acceptable modeling accuracy and effort This paper summarized and compared the regions based on data available in the literature